2018
DOI: 10.1002/cmdc.201800647
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanoswitchable Inhibitors of Protein–Protein Interactions Involved in Apoptosis

Abstract: Progress in drug delivery is hampered by a lack of efficient strategies to target drugs with high specificity and precise spatiotemporal regulation. The remote control of nanoparticles and drugs with light allows regulation of their action site and dosage. Peptide‐based drugs are highly specific, non‐immunogenic, and can be designed to cross the plasma membrane. In order to combine target specificity and remote control of drug action, here we describe a versatile strategy based on a generalized template to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…30 These properties are appealing for photopharmacology, which aims at controlling drug action on demand at selected locations using light, to enable precise responses and reduce unwanted side effects of treatments, or to manipulate specific cell types and neural circuits for investigational purposes. 31,32 Many photoswitchable bioactive molecules have been reported that offer high pharmacological specificity and potency for a diversity of targets, including ion channels, 33−36 G protein-coupled receptors, 37−39 protein−protein interactions, 40,41 and enzymes. 42−45 Most are based on aryl azo compounds, 46−48 which are difficult to isomerize using orange−red light without introducing substituents that often perturb the pharmacological properties of the original compound.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 These properties are appealing for photopharmacology, which aims at controlling drug action on demand at selected locations using light, to enable precise responses and reduce unwanted side effects of treatments, or to manipulate specific cell types and neural circuits for investigational purposes. 31,32 Many photoswitchable bioactive molecules have been reported that offer high pharmacological specificity and potency for a diversity of targets, including ion channels, 33−36 G protein-coupled receptors, 37−39 protein−protein interactions, 40,41 and enzymes. 42−45 Most are based on aryl azo compounds, 46−48 which are difficult to isomerize using orange−red light without introducing substituents that often perturb the pharmacological properties of the original compound.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The hurdles to operate DASAs in aqueous solutions are most aggravating since they are native red/NIR-absorbing, negative photochromic compounds that would afford low scattering and deep penetration in tissue without incurring phototoxicity in biological applications . These properties are appealing for photopharmacology, which aims at controlling drug action on demand at selected locations using light, to enable precise responses and reduce unwanted side effects of treatments, or to manipulate specific cell types and neural circuits for investigational purposes. , Many photoswitchable bioactive molecules have been reported that offer high pharmacological specificity and potency for a diversity of targets, including ion channels, G protein-coupled receptors, protein–protein interactions, , and enzymes. Most are based on aryl azo compounds, which are difficult to isomerize using orange–red light without introducing substituents that often perturb the pharmacological properties of the original compound. Photoswitching with continuous NIR light has been achieved in diazocines and using two-photon (2P) excitation of simple azobenzenes ,, in neurons, but the latter requires pulsed lasers and precision optics. , Thus, developing compounds that can be directly photoswitched in vivo with continuous-wave red or NIR light using portable devices (e.g., LEDs) remains an unmet need in basic and applied photopharmacology. They would enable noninvasive drug-based phototherapies and facilitate their translation to the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the free amino group from the N‐terminus of the acceptor featuring an oligoglycine chain performs a nucleophilic attach at the acyl intermediate, thus forming a link between the acyl donor and acceptor. The only requirement for the acceptor is the presence of an oligoglycine chain, preferably of more than two glycines, [103] which can perform the nucleophilic attack to the acyl‐SrtA intermediate [89,100] . A critical prerequisite for the photoswitch to be used in this ligation, especially to modify intact complex proteins, is its solubility in water, as most proteins do not tolerate large amounts of organic co‐solvents [72,73] .…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly applied solubilization approach is by introducing sulfonate groups to enable dissolving the lipophilic aromatic switch core in water, as in the most widely used water-soluble azobenzene 3,3'-bis(sulfonate)-4,4'bis(chloroacetamido)azobenzene (BSBCA) [74] (Figure 1a) that has been applied to cross-link various targets. [42,[75][76][77][78][79][80][81][82][83] The numerous applications of BSBCA include cross-linking of smaller helical peptides that interact with larger targets, such as the S-peptide which forms the RNase S complex, [84][85][86] to study allosteric regulation mechanisms of the PDZ domains, [80,87] control the DNA binding activity of alpha-helical peptides [79,81,88,89] or inhibit protein-protein interactions in living cells, [78] as well as to activate fluorescence of a reporter peptide in zebrafish. [90] BSBCA was used to cross-link many helical peptides, [75] yet only one type of small protein target, fynomers.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have inspired the advances in other novel methods of investigating peptide inhibitors. For example, Gorostizaa and Ernest Giralt group have recently conceived a modular design strategy based on a generalized template (GT) to obtain nano-switchable peptides that can be applied to α-helix mediated PPIs (Nevola et al, 2019 ). They used the GT peptide approach combining the structural information from the PPI hot spots and finally developed series of light-regulated peptide inhibitors targeting Bcl-xL and Bak.…”
Section: Examples Of Peptide-based Ppi Inhibitorsmentioning
confidence: 99%